Diversidade e estabilidade das comunidades de macrófitas aquáticas em dois ambientes subtropicais. - Carvalho, Priscilla de (2009)
The analysis of temporal community changes is a key issue in ecology. Researches about community stability highlighted the influence of disturbance events of different frequency and intensity. In this way, long-term ecological research is valuable to assess temporal community changes and to understand disturbance dynamics. In addition, we can realize how community development follows a disturbance, due to the pre and pos disturbance data. Ecologists have also raised the interest about the relationship between biodiversity and community stability/resilience after a disturbance. The main goal of this study was to analyze the temporal stability of the aquatic macrophyte communities in two subtropical ecosystems: the Itaipu Reservoir and the Upper Paraná River floodplain. We explored a long-term data set from eight years (Itaipu Reservoir) and six years (floodplain). The relationship between diversity and stability was also discussed, and was the main focus in an experiment conducted in situ in the Paraná River floodplain. Thus, this study was divided into three chapters. The first one entitled "Diversity and stability of aquatic macrophyte communities in the Itaipu Reservoir" had the aim to measure the effects of water level drawdown (a rare disturbance) on the aquatic macrophyte communities. In the second chapter entitled "Stability of aquatic macrophyte communities: a long-term study in the Upper Paraná River floodplain", the vegetation dynamics were studied between 2002 and 2008 and we attempted to evaluate the influence of two extreme flood disturbance on these communities. Finally, in the third chapter entitled "Diversity increases the resilience of aquatic macrophyte communities: an in situ experimental approach", we conducted a field manipulation in the Paraná River floodplain to assess the effect of diversity on community resilience (stability) following a disturbance (removed vegetation). Our long term data analyses suggested that the aquatic macrophytes communities in the Itaipu Reservoir and in the Paraná River floodplain are dynamics, with constant changes in the frequency of species along time. The submersed species had the lower resistance following the disturbances. The experiment conducted in situ supported the hyphothesis that communities with higher species diversity has faster recover in plant biomass and thus, is more resilient in response to disturbance.